The Implications of Digital Marketing on Business Performance - Oana PRICOPOAIA; Adrian MICU; Irina Olimpia SUSANU (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2022)
The correct application of digital marketing strategies has a direct impact on favorable results within a business. Social media marketing is not just a trend for a long time, now it has become a necessity, the company that stays only with traditional advertising can lose both existing customers and potential customers. The purpose of the conducted research is to identify among young entrepreneurs the motivations for using the concept of content marketing in their business, the role of social media networks in promoting a business, the evaluation of the impact of following a digital marketing plan on the final results of the company, the analysis of the implications of using tools of digital marketing and the need to establish digital marketing channels at the level of a business. We are witnessing an extraordinary evolution of marketing and how it is understood, applied and quantified through the results achieved. Digital marketing has become indispensable for all entrepreneurs, and in order to cope with the market in which they operate in relation to the numerous competitions and the increasingly sophisticated demands of consumers, entrepreneurs take into account the digital marketing channels suitable for their business, designing and following a guide of digital marketing and the use of effective digital marketing tools.